(untitled) - Narasimhan, S V. (Harrow, U.K., 2005)
Signal Processing: Principles and Implementation, has been developed in a simple logical manner. To understand the subject, knowledge of junior level Physics and Mathematics is required. The ease of understanding is not at the cost of the rigor and depth of the subject but has been achieved by giving all the intermediate mathematical steps involved in a derivation and by giving the physical meaning of the mathematical relations.
Keywords: Lý thuyết thông tin,Information theory; Tạo lập dữ liệu,Data processing